Experiências a/r/tobiográficas: diálogos narrativos sobre a formação de arte/educadoras - Bezerra, Larissa Rogério (2022)
This thesis is not just an academic work, it is above all things, an invitation. It is an invitation to walk through stories, places, events, reflections, images, expressions, provocations and opportunities. The main objective of this work is to identify and reflect on the meanings of the experiences in art, inscribed in the life stories of art/educators, seeking to understand their role in the formation of the artist/researcher/teacher. In that matters, we chose to create a visual and textual metaphor between the act of researching and walking, so that reading could be an artistic, aesthetic, biographical and formative experience. Inspired by the scenic understanding (MARINAS, 2007), the data analysis and the development of the path were organized and divided into three tracks. On track 01, we met the art group/educators who participated in this research and got to know the methodological scenarios composed by the (Auto)Biographic Research in Education (JOSSO, 2010; DELORY-MOMBERGER, 2014) and by the Art Based Educational Research – A/r/tography (IRWIN, 2013; DIAS, 2013), understanding the scripts that directed us to create the A/r/tobiographical Experience. On track 02, we present the narrative dialogues and biographical artistic artifacts, through a structure inspired by the “talking books” idealized and written by Freire (2011), where we build together the meanings of the experiences lived and narrated by the art/educators. Our main guides on this journey were: Freire (2015, 2019, 2021), Larrosa (2002), Barbosa (2010, 2011), Boal (2009), Ferraz and Fusari (2018) and Duarte Jr. (2012). On track 03, we visit the implicit paths and silent words found in the narrative dialogues, built during the work, believing that the in-between spaces, fissures, shadows and silences bring powerful meanings to understand what was narrated. At the end of the way, we realized that Juliana, Eloilma, Adriano, Mirian and Sara, with their life stories, taught us about the revolutionary power of art, the relevance of empathy in the learning process, art/education as a liberating experience, the need to deconstruct pre established concepts so that we can see new perspectives and the importance of reflecting on our trajectory so that we can understand who we are today. From the path followed, we understand that the A/r/tobiographical Experience is an opportunity to reflect on artistic, investigative and teaching practices, leading us to a better understanding of the artist/researcher/teacher identity and the social and educational history of our country.